Immediate-early transcription of Herpesvirus saimiri. - Bodemer, W (1984)
Transcription of Herpesvirus saimiri was characterized during the initial phases of productive infection by Northern blot analyses and hybridizations of radioactive cDNA with cloned fragments of virion L-DNA. Under conditions of immediate-early transcription, e.g., blocking of viral protein synthesis by cycloheximide, a single cytoplasmic polyadenylated viral RNA of 2.7 kilobases was found in infected cells. The sequence coding for this RNA was between map units 0.89 and 0.93; it was transcribed from right to left in prototype arrangement of M-DNA. The immediate-early mRNA of lytically infected cells appeared to be very similar, if not identical, to the single viral RNA species found in lymphoid cells transformed by H. saimiri.